2016
DOI: 10.1016/j.ajhg.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Mutations in TMEM126B Cause Severe Complex I Deficiency with a Variable Clinical Phenotype

Abstract: Complex I deficiency is the most common biochemical phenotype observed in individuals with mitochondrial disease. With 44 structural subunits and over 10 assembly factors, it is unsurprising that complex I deficiency is associated with clinical and genetic heterogeneity. Massively parallel sequencing (MPS) technologies including custom, targeted gene panels or unbiased whole-exome sequencing (WES) are hugely powerful in identifying the underlying genetic defect in a clinical diagnostic setting, yet many indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…Autosomal recessive mitochondrial complex I deficiency (MCID) accounts for approximately 23% of childhood respiratory chain deficiency cases [1]. Mitochondrial complex I is composed of 44 structural subunits and over 10 assembly factors, which underscores its diverse clinical manifestations that diverge based on severity and age of onset [2]. The clinical presentations range from infant onset subacute necrotizing encephalomyelopathy (Leigh syndrome [MIM: 256000]) to adult-onset exercise-induced myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal recessive mitochondrial complex I deficiency (MCID) accounts for approximately 23% of childhood respiratory chain deficiency cases [1]. Mitochondrial complex I is composed of 44 structural subunits and over 10 assembly factors, which underscores its diverse clinical manifestations that diverge based on severity and age of onset [2]. The clinical presentations range from infant onset subacute necrotizing encephalomyelopathy (Leigh syndrome [MIM: 256000]) to adult-onset exercise-induced myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Following identification of TMEM126B as a complex I assembly factor, two groups reported biallelic mutations in a cohort of undiagnosed complex I-deficient patients. Mutations were identified by either whole-exome sequencing or targeted NGS, and their pathogenicity was validated by blue native polyacrylamide gel electrophoresis and Western blotting of patient tissues (1,77).…”
Section: Figurementioning
confidence: 99%
“…Indeed, individuals with mutations in TMEM126A primarily present with optic atrophy and most have been identified with homozygous nonsense mutations (Hanein et al, 2009;Meyer et al, 2010). This is in contrast to individuals with TMEM126B mutations who present with adult onset myopathy and all identified cases have at least one missense mutation, suggesting total ablation of TMEM126B may not be compatible with human life (Alston et al, 2016;Sánchez-Caballero et al, 2016b). One possibility is that TMEM126B plays a crucial role in the MCIA complex for ND2-module assembly, while other (unidentified) mitochondrial machineries may be able to compensate for the loss of TMEM126A for ND4-module assembly.…”
Section: Duplication and Specialization Of The Tmem126 Locusmentioning
confidence: 79%
“…The MCIA complex is involved in assembly of the ND2 membrane module (Formosa et al, 2020;Guerrero-Castillo et al, 2017). While it has been suggested that TMEM126A may play a compensatory role in patient cells with mutations in TMEM126B (Sánchez-Caballero et al, 2016b), the clinical presentation of the two markedly differ (AROA vs late onset myopathy) (Alston et al, 2016). Nevertheless, a role for TMEM126A in complex I assembly may be implicated given that it was found enriched with the complex I assembly factors DMAC1 (Stroud et al, 2016), TMEM186 and COA1 (Formosa et al, 2020), as well as with the general mitochondrial insertase OXA1L (Thompson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%